2021
DOI: 10.1111/jce.15329
|View full text |Cite
|
Sign up to set email alerts
|

Conduction system pacing versus biventricular pacing: Reduced repolarization heterogeneity in addition to improved depolarization

Abstract: Introduction: His-bundle pacing (HBP) and left-bundle-area pacing (LBAP) are conduction system pacing (CSP) modalities increasingly used as alternatives to conventional biventricular pacing (BiVP). While effects of CSP on ventricular depolarization have been reported, effects on ventricular repolarization have not. Methods: QRS duration (QRSd) and validated ECG parameters of ventricular repolarization associated with arrhythmic risk (T-peak-to-T-end Transmural , T-peak-to-Tend Total , T-peak dispersion, QTc, Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Furthermore, pacing at such sites of reticular arrangement may allow for a larger `` virtual electrode 27 , which may then allow for more rapid delivery of electrical depolarization and significantly shorten the QRS duration 28 . Finally, LBBP and HBP have both been proven to result in more physiologic repolarization as compared to BiVP, with improved QT and T‐peak‐to‐T‐end intervals (a measure of transmural dispersion of repolarization), possibly translating to lower proarrhythmic risk 29 . Thus, LBBP may offer excellent ventricular electrical synchrony, which can be crucial for improving cardiac function and reducing HF symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pacing at such sites of reticular arrangement may allow for a larger `` virtual electrode 27 , which may then allow for more rapid delivery of electrical depolarization and significantly shorten the QRS duration 28 . Finally, LBBP and HBP have both been proven to result in more physiologic repolarization as compared to BiVP, with improved QT and T‐peak‐to‐T‐end intervals (a measure of transmural dispersion of repolarization), possibly translating to lower proarrhythmic risk 29 . Thus, LBBP may offer excellent ventricular electrical synchrony, which can be crucial for improving cardiac function and reducing HF symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study demonstrated that conduction system pacing in comparison to biventricular pacing resulted in improved parameters of repolarization as well as resolution of T-wave memory. 21 …”
Section: Discussionmentioning
confidence: 99%
“…They reported that left bundle branch area pacing yielded a narrower paced QRS duration, shorter QT and QTc interval, lower QT dispersion, and shorter Tpe than RV septal pacing in the acute phase after pacemaker implantation. Recent studies demonstrated the significant benefits of repolarization parameters on ECG after conduction system pacing compared with those after cardiac resynchronization therapy at a mild‐term assessment period of up to 6 weeks or a median of 42 days following implantation (Gupta & Pavri, 2022 ; Sarkar et al, 2022 ). In contrast to previous studies, we implemented a sufficient follow‐up period of 6 months to reduce the effect of ventricular repolarization instability during the acute phase and elicited a continuous advantage of repolarization stability after HBP in the chronic phase.…”
Section: Discussionmentioning
confidence: 99%